The contribution of the output gap to the conduct of inflation targeting in the Philippines - Angeles, Rj F.; Tan, Margot Aissa C. (The Philippine Review of Economics, 2007)
This paper evaluates whether the inclusion of the output gap in the central bank's estimated reaction function would improve the conduct of inflation targeting in the Philippines. A reduced-form vector autoregression model was constructed using exchange rate, output gap, inflation, and interest rate as the relevant variables. The authors use two measures for the short-term interest rate: the reverse repurchase rate and the T-bill rate. Results from counterfactual simulations show that the adoption of a Taylor-type rule, which involves the use of the output gap, minimizes the deviations of inflation from its target. Based on the empirical results of this study, the inclusion of the output gap is significant in terms of its contribution to maintaining inflation at a level that is nearer to the desired target. It is recommended that further studies consider the use of output gap estimates derived from other procedures, especially those that employ Markov-regime switching techniques, which could account for shocks in the economy. In addition, the use of alternative model-representations for the Philippine economy within which counterfactual simulations may be performed is recommended as an area for future research.